Taxes in the Price Equation: Textiles and Rubber - Moffat, William R. (The Review of Economics and Statistics, 1970)
CONOMETRIC studies of absolute prices have generally ignored the corporation income tax as a possible explanatory variable; the public finance literature on the other hand contains much speculation that pricing might be affected by the tax, though it offers little empirical evidence. This paper draws on work in both fields to develop and test tax-price hypotheses against data from the textile and rubber industries. Analysis of price change involves linking the influences of supply and demand. The standard sources of hypotheses about the links are the theories of competition and monopoly. In both cases, the parameters of cost and utility ultimately determine price and quantity, but the emphasis differs as to what are the important decisions of firms in the process. The competitor is a price-taker who decides what quantity to supply; the monopolist may be either a price-taker, or a price-maker whose decision is what price to charge. It seems a common fact of observation that most industrial firms are price-makers who supply the resulting demand, and not vice versa, so for an analysis of prices of such products, monopoly theory is likely to be more fruitful of hypotheses than competitive theory. Our procedure therefore is to regard the industry as a monopolistic firm, and to deduce what industry data would show if this firm followed alternate simple pricing rules: profit maximization, target rate of return, percentage markup over variable costs, and sales maximization subject to a minimum rate of profit. Each rule is formulated in both taxfree and tax-influenced form. Textiles and rubber were chosen both for reasons of data convenience, and because they differ considerably in structure. Yearly data for 1924 through 1962 were drawn from the Treasury Department's Statistics of Income for Corporations, supplemented by the Bureau of the Census Annual Survey of Manufactures and Census of Manufactures, and by Bureau of Labor Statistics indexes of wholesale prices, wages and employment. The time period and data sources were dictated by the need to include both financial and operating information, and periods of both high and low tax rates. Several adjustments were made to the data, the most important of which was to remove, in the interests of sample homogeneity, Miscellaneous Plastics from rubber and Apparel from textiles. Hence the industries are somewhat narrower than those of the published two-digit Standard Industrial Classification. The war years 1942 through 1946, 1951 and 1952 were omitted from all regressions. Lags, differencing, and lack of early-year information restricted the final sample to 1928 through 1962 for rubber, and 1927 through 1962 for textiles. Yearly data for industry aggregates have obvious drawbacks for investigation of this sort. The aggregates are quite broad, and if pricing patterns are discernible in them, the patterns must be generated by average behavior over heterogeneous groups of products. Yearly observations provide little basis for studying lags. But it is an unfortunate reality that most econometric work on prices has been at even higher levels of aggregation than this. One can only caution that all results, including these, must be assessed in the light of the data weaknesses.